2021
DOI: 10.1108/ijrdm-07-2020-0239
|View full text |Cite
|
Sign up to set email alerts
|

E-retailer cognitive and emotional relationship quality: their experiential antecedents and differential impact on brand evangelism

Abstract: PurposeLimited knowledge exists on the difference in the antecedents and outcomes of relationship quality's cognitive and emotional aspects for e-retailers. This research tests how utilitarian and hedonic shopping values differentially affect “cognitive and emotional” relationship quality components and how the latter differentially affects word-of-mouth and brand evangelism.Design/methodology/approachOnline survey data were collected from 450 Jordanian online shoppers. Structural equation modeling (AMOS 24.0)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 85 publications
2
20
0
Order By: Relevance
“…Kumar and Kaushik (2020) argue that experience plays the main role in forming brand the engagement—brand evangelism duality. Al Nawas et al (2021) go further and exploit the direct relationship between brand experience and brand evangelism. Experience is also focal in the framework for creation of brand evangelists proposed by Kang et al (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kumar and Kaushik (2020) argue that experience plays the main role in forming brand the engagement—brand evangelism duality. Al Nawas et al (2021) go further and exploit the direct relationship between brand experience and brand evangelism. Experience is also focal in the framework for creation of brand evangelists proposed by Kang et al (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kang et al (2020) investigated brand evangelism by examining positive and oppositional referral intentions through brand attachment and brand distinctiveness. Al Nawas et al (2021) revealed that emotional relationship quality plays an essential role in developing brand evangelists, and Mansoor and Paul (2022) evaluated brand evangelism through masstige brands and brand happiness. However, there is a dearth of research on brand evangelism in the financial sector, particularly in the Vietnamese banking industry.…”
Section: Brand Evangelismmentioning
confidence: 99%
“…Despite the fact that previous research has demonstrated that highly religious adherents behave differently and have their own criteria in purchasing decisions (Amir, 2021), Al Nawas et al (2021) noted that there is a lack of research in consumer research that can prove the effect of religiosity in changing consumer patronage behaviour specifically in the context of Muslim consumers. Moreover, empirical study on these concepts in consumer behaviour has been scarce, and its significance in the field is still not widely recognised.…”
Section: Problem Statementmentioning
confidence: 99%
“…Further study is required to disprove the claim that customers' religious beliefs and practises influence the criteria they use to assess items and services (Ha et al, 2014). Observable aspects of religion, as well as the importance of consumer behaviour to the success of marketers and retailers, suggest the need for further research into religious faith (Al Nawas et al, 2021).…”
Section: Problem Statementmentioning
confidence: 99%